Association Between Cigarette Smoking and Breast Milk Levels of Nesfatin-1, Irisin, and Oxidative Stress Markers - Yildiz, Nesibe; Yilmaz, Adnan; Iskender, Hatice; Dokumacioglu, Eda (Makara Journal of Health Research, 2021)
Background: Breast milk is a very important functional food in the prevention of metabolic and chronic diseases. This study aimed to investigate the effects of smoking during pregnancy on the concentrations of nesfatin-1, irisin, and oxidative stress markers in breast milk. Methods: This study included two groups of 14 smoking and 14 nonsmoking mothers. Malondialdehyde (MDA) level and superoxide dismutase (SOD) activity were measured according to the spectrophotometric method in breast milk samples. Nesfatin and irisin levels were measured by enzyme-linked immunosorbent assay. Results: Levels of nesfatin-1 and MDA of the smoking group were significantly higher than those in the control group (p < 0.001). The SOD activity of the smoking group was significantly lower than that of the control group (p < 0.001). No significant difference was found in the breast milk irisin level between the study groups (p > 0.050). Conclusions: Cigarette smoking increases MDA level and decreases SOD activity in breast milk. Nesfatin-1 levels would increase in accordance with increased oxidative stress, and nesfatin-1 acts as a protective mechanism to limit oxidative damage.